Peranan sistem informasi akuntansi dalam menunjang efektivitas pengendalian internal pemberian kredit di PT. Bank Sulutgo Cabang Airmadidi - Manongga, Junaldi (Yayasan Widyantara Nawasena Raharja, 2025)
Credit is a service provided by banks to channel funds to customers or prospective debtors. To provide credit, the bank will analyze whether the prospective debtor is worthy of being given credit through various considerations. The role of the Accounting Information System is very important in making decisions about whether credit can be granted or not. This research is qualitative research using primary and secondary data types. This research method is descriptive. The research results show that in carrying out credit granting activities, PT Bank Sulut Go Airmadidi Branch has been able to implement an accounting information system for granting credit adequately as seen from employees who are competent in the credit sector, the tools used are sufficient, namely using tools that support the credit granting process, clear methods and procedures starting from the credit application stage to supervision and guidance of debtors. Thus, the implementation of internal control over lending can also be said to be effective.